Perception of Zero Waste in the Context to Environmental Innovation in Slovakia - Loučanová, Erika (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
At the present time, a great attention is paid to the ecological innovation, which represents innovation characterization to any ecological change with a positive impact on consumers. Such innovations increase the comfort for consumers and concurrently they represent more effective, more economic, ecological, healthier and safer solutions. Ecological innovation represents any innovation aimed at significant and visible progress towards the goal of sustainable development. This is done by reducing the impact on the environment or achieving a more efficient and responsible use of natural resources, including energy and Zero waste. The aim this paper is evaluation to the perception of Zero waste in the context of ecological innovations in Slovakia. The research is carried out using the Kano model. The results point to the importance of addressing the issue of ZeroWaste, encouraging friends to buy in non-packaging stores and creating a stimulation of advertising to buy products in a non-packaging store. Other attributes of the given issue are perceived by Slovak respondents in the opposite way or have no influence on them. Therefore, it is important to provide sufficient information on this issue and to educate the population in order to increase their interest in this issue and to start behaving responsibly towards waste management.